The UK's membership in European Economic Community (EEC) and EU from the economical and political point of view between the two referenda in 1975 and 2016. - Veselá, Markéta (2017)
The aim of this thesis is to asses and analyse the membership of the UnitedKingdom of Great Britain and Northern Ireland (UK) of the European Union (EU) from1975 until 2016. The thesis provides an analysis of the main areas of interest ofreferendum in 1975 which are: economic impact of the UK’s membership on itsdevelopment; impact of the membership on the agriculture, food and fisheries;preservation or sacrifice of the British sovereignty and the length of the UK’s membershipof the European Economic Community (EEC). The similar areas were identified for thereferendum in 2016 with an exception of the topic of immigration. It also comprises ananalysis and confirmation of an impact of the immigration crisis display in the Britishmedia on the result of the referendum in 2016. The thesis also contains an analysis of theUK’s member contribution to the EU budget which has been always, with an exceptionof one year, higher than the funding obtained from the EU programs. There are alsopresented the continuities, similarities, and differences which are the reasons for theircontradictory results. These are diverse historical background, unwillingness to sacrificea part of its sovereignty and the long-running frustration from the EU’s restrictionsaccompanied by the media pressure.